Definitions of Frailty in Qualitative Research: A Qualitative Systematic Review - Deborah A. Lekan; Susan K. Collins; Audai A. Hayajneh (Journal of Aging Research)
The purpose of this qualitative systematic review was to examine how frailty was conceptually and operationally defined for participant inclusion in qualitative research focused on the lived experience of frailty in community-living frail older adults. Search of six electronic databases, 1994–2019, yielded 25 studies. Data collection involved extracting the definition of frailty from the study aim, background, literature review, methods, and sampling strategy in each research study. Quality appraisal indicated that 13 studies (52%) demonstrated potential researcher bias based on insufficient information about participant recruitment, sampling, and relationship between the researcher and participant. Content analysis and concept mapping were applied for data synthesis. Although frailty was generally defined as a multidimensional, biopsychosocial construct with loss of resilience and vulnerability to adverse outcomes, most studies defined the study population based on older age and physical impairments derived from subjective assessment by the researcher, a healthcare professional, or a family member. However, 13 studies (52%) used objective or performance-based quantitative measures to classify participant frailty. There was no consistency across studies in standardized measures or objective assessment of frailty. Synthesis of the findings yielded four themes: Time, Vulnerability, Loss, and Relationships. The predominance of older age and physical limitations as defining characteristics of frailty raises questions about whether participants were frail, since many older adults at advanced age and with physical limitations are not frail. Lack of clear criteria to classify frailty and reliance on subjective assessment introduces the risk for bias, threatens the validity and interpretation of findings, and hinders transferability of findings to other contexts. Clear frailty inclusion and exclusion criteria and a standardized approach in the reporting of how frailty is conceptually and operationally defined in study abstracts and the methodology used is necessary to facilitate dissemination and development of metasynthesis studies that aggregate qualitative research findings that can be used to inform future research and applications in clinical practice to improve healthcare.